The influence of e-leadership on employee motivation while working from home during crisis - Mohd@Ariffin, Juliza Adira; Md Rami, Ahmad Aizuddin (Human Resource Management Academic Research Society, 2023)
Work from home (WFH) implies that employees perform tasks from their respective homes, with virtually no interaction between leader and employee. According to previous literature, organisations began implementing WFH in the 1970s, but in Malaysia, large-scale implementation of work-from-home policies began with the spread of the Covid-19 pandemic in 2019. The purpose of this study is to determine how middle-level leaders' implementation of e-leadership affects employee motivation in three departments of the Malaysian Ministry of Education (MOE). The quantitative methods of surveys were used to collect data for this study. A questionnaire was used as a research tool, with 94 employees participating out of a total population of 124. The data collected for this study were analysed using IBM SPSS statistics version 22 to perform simple linear regression analysis and descriptive analysis. The results of the study show that e-leadership has a great impact on employee motivation when working from home during a crisis. This finding suggests that MOE needs to pay attention to e-leadership practised among middle leaders especially when employees work from home during a crisis since employee motivation is the key to organizational development nowadays.